(untitled) (Jurnal AbdiMas Nusa Mandiri, 2026)
Micro, Small, and Medium Enterprises (MSMEs) are the main drivers of the economy in Garut Regency. However, many Generation Z entrepreneurs still face marketing challenges due to the suboptimal use of digital platforms. On the other hand, the development of e-commerce provides great opportunities to expand market access and strengthen business competitiveness. The purpose of this community service activity is to increase the understanding and motivation of Generation Z MSME entrepreneurs in utilizing e-commerce. The method used is interactive socialization through face-to-face meetings with material on e-commerce utilization, promotion techniques, and social media integration. The data shows that 35 participants from the culinary, fashion, MUA, and grocery store sectors took part in the activity. The evaluation was conducted using Pre-Test and Post-Test instruments. The results of the activity showed a significant increase in the average understanding score of the participants from 45% to 85%, with a participation rate of 90%. The tangible impact was evident in the strong intention of 85% of the participants to activate their online stores after the activity. In conclusion, this activity successfully provided a strong foundation of digital literacy for Generation Z MSMEs, although follow-up in the form of practical training and ongoing mentoring is needed to have a real impact on their business performance in the digital ecosystem.